2003
DOI: 10.1046/j.1365-2141.2003.04153.x
|View full text |Cite
|
Sign up to set email alerts
|

A validated decision model for treating the anaemia of myelodysplastic syndromes with erythropoietin + granulocyte colony‐stimulating factor: significant effects on quality of life

Abstract: Summary. We have published previously a prototype of a decision model for anaemic patients with myelodysplastic syndromes (MDS), in which transfusion need and serum erythropoietin (S-Epo) were used to define three groups with different probabilities of erythroid response to treatment with granulocyte colony-stimulating factor (G-CSF) + Epo. S-Epo £ 500 U/l and a transfusion need of < 2 units/month predicted a high probability of response to treatment, S-Epo > 500 U/l and ‡ 2 units/month for a poor response, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
273
4
14

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(299 citation statements)
references
References 28 publications
8
273
4
14
Order By: Relevance
“…18 In anemic patients with myelodysplastic syndromes (MDS), G-CSF and erythropoietin may synergistically improve hemoglobin levels and reduce marrow progenitor apoptosis. [19][20][21] We have earlier shown that G-CSF decreases cytochrome c release from mitochondria to cytosol, thereby reducing caspase activation and premature death of cultured MDS erythroblasts. 22,23 However, the precise mode of the antiapoptotic action of G-CSF is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…18 In anemic patients with myelodysplastic syndromes (MDS), G-CSF and erythropoietin may synergistically improve hemoglobin levels and reduce marrow progenitor apoptosis. [19][20][21] We have earlier shown that G-CSF decreases cytochrome c release from mitochondria to cytosol, thereby reducing caspase activation and premature death of cultured MDS erythroblasts. 22,23 However, the precise mode of the antiapoptotic action of G-CSF is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Response rates reach 60% in MDS with low baseline serum erythropoietin (EPO) level (o200-500 U/l), low transfusion requirement (o2 RBC/month) and low or intermediate-1 IPSS. 7,8 Thus ESAs, with or without G-CSF, are considered first-line treatments of anemia of MDS with low and intermediate-1 IPSS (except in patients with 5q deletion, where lenalidomide is more effective). 9 All-trans retinoic acid (ATRA) is a vitamin A derivative involved in normal hematopoiesis, particularly in terminal granulocytic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…4). 46 Combinations of Epo with all-transretinoic acid (ATRA) have shown activity that results not only in erythroid but also in neutrophil and platelet responses. 47 Combinations of erythropoietic proteins and thalidomide have resulted in a high incidence of thromboembolic complications and, thus, should be used with caution.…”
Section: Hematopoietic Growth Factorsmentioning
confidence: 99%